2018
DOI: 10.3390/ma11010115
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Mixed Thick-/Thin Film Microgenerators Based on Constantan/Silver

Abstract: This paper describes the design, manufacturing and characterization of newly developed mixed thick-/thin film thermoelectric microgenerators based on magnetron sputtered constantan (copper-nickel alloy) and screen-printed silver layers. The thermoelectric microgenerator consists of sixteen thermocouples made on a 34.2 × 27.5 × 0.25 mm3 alumina substrate. One of thermocouple arms was made of magnetron-sputtered constantan (Cu-Ni alloy), the second was a Ag-based screen-printed film. The length of each thermocou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The experiments showed that for a fixed P × d-value, there is an increasing deviation |∆S| from the bulk value as the film grows thinner. A similar observation was done by Gierczak et al [27]. This is a classic observation of the size-effect.…”
Section: Discussionsupporting
confidence: 82%
“…The experiments showed that for a fixed P × d-value, there is an increasing deviation |∆S| from the bulk value as the film grows thinner. A similar observation was done by Gierczak et al [27]. This is a classic observation of the size-effect.…”
Section: Discussionsupporting
confidence: 82%
“…For calculations related to forced convection, the values for the assumed cooling air temperature of the system was used ( T air = 20 °C). For free convection, temperature T AV was used, where:TAV=TCPU+Tair2=70+202=45 onormalC.This is the arithmetic mean of the maximum surface temperature of the heat sink ( T CPU ) and the cooling air ( T air ) [26].…”
Section: Table A1mentioning
confidence: 99%
“…This is the arithmetic mean of the maximum surface temperature of the heat sink ( T CPU ) and the cooling air ( T air ) [26].…”
Section: Table A1mentioning
confidence: 99%
“…The Zn-Sb binary material is made of ZnSb and β-Zn 4 Sb 3 which are promising P -type thermoelectric materials for low-cost energy production, intended to use at intermediate range of temperatures (between room temperature and 350 °C) [8]. Thin film technique can be an appropriate method for upgrading the properties of thermoelectric materials due to low dimensional quantum confinement [9,10,11,12,13]. The properties improvement of thin film TE materials has introduced a great potential in different applications such as miniaturized sensors, micro power sources, and other low power applications.…”
Section: Introductionmentioning
confidence: 99%